Autophagy Activation by Hypoxia Regulates Angiogenesis and Apoptosis in Oxidized Low-Density Lipoprotein-Induced Preeclampsia - Li, Yamei; Zhao, Xueya; He, Biwei; Wu, Weibin; Zhang, Huijuan; Yang, Xingyu; Cheng, Weiwei (Frontiers in Molecular Biosciences, 2021)
Objective: Autophagy influences a wide range of physiological and pathological processes in human body. In this study, we aimed to investigate the role of autophagy in early-onset preeclampsia (EOPE): autophagy activation by hypoxia could rescue impaired angiogenesis and apoptosis in preeclampsia leading by ox-LDL. Methods: Transmission electron microscopy was applied to identify autolysosomes in trophoblasts cells of placenta apical region. Quantitative Real-Time Polymerase Chain Reaction, Western blot, Flow cytometry and Wound-healing Assays were adopted to determine autophagy activity, angiogenesis and apoptosis in placenta tissues or HTR8/SVneo cell. Results: Autophagy activity was inhibited in women placenta that experienced EOPE; autophagy activation by hypoxia enhanced the migration ability, rescued ox-LDL mediated impaired angiogenesis in HTR8/SVneo cells: vascular endothelial growth factor A (VEGFA), downregulation FMS-like tyrosine kinase-1 (FLT1) upregulation; and protected against cell apoptosis (BAX downregulation). Conclusion: Autophagy could maintain the function of trophoblast cells by differentially regulating the expression of VEGFA and FLT1, protecting against cell apoptosis at the maternal-fetal interface, potentially related to prevention of preeclampsia.